Ethnic mortality differentials in Lithuania: contradictory evidence from census-linked and unlinked mortality estimates. Issue 6 (13th June 2011) - Jasilionis, Domantas; Stankuniene, Vlada; Ambrozaitiene, Dalia; Jdanov, Dmitri A; Shkolnikov, Vladimir M
Abstract : Background: This study examines discrepancies between census and death registry information in the reporting of the ethnicity of the deceased in Lithuania and shows how these reporting differences influence estimates of mortality inequality by ethnicity. Methods: This study uses a census-linked dataset provided by Statistics Lithuania. The data include all deaths and population exposures between 1 July 2001 and 31 December 2004. The information on the ethnicity of the deceased was available from both the census and the death records. The Poisson regression was applied (1) to measure the effects of socio-demographic variables on the misreporting of ethnicity on death records and (2) to estimate mortality rate ratios by ethnicity based on census-linked and unlinked data. Results: The death-record-based information on ethnicity under-reports the deaths of people of Russian, Polish and other ethnicities and over-reports the deaths of people of Lithuanian ethnicity. This leads both to the underestimation of mortality in the three ethnic minority groups and to biased mortality rate ratios. The misreporting is higher in death records for women, persons younger than 80 years, divorced persons, urban residents and those dying from ill-defined causes. Conclusion: Studies based on unlinked data may provide biased estimates of ethnic mortality differences.